Diagnostic validity of premenstrual dysphoric disorder: revisited - Naik, Shalini S.; Nidhi, Yadav; Kumar, Krishan; Grover, Sandeep (Frontiers in Global Women's Health, 2023)
Legitimizing the distress and socio-occupational impairment experienced by women with Premenstrual dysphoric disorder (PMDD), the World Health Organization (WHO) and American Psychiatric Association (APA) deemed it as an Independent diagnostic entity while it still remained inexplicit whether it is a valid diagnosis from a biological point of view. This illness has also been criticized for a feminist-led, sympathetic reaction to the modern cultural challenges of urban, literate, employed, high-functioning women. This article systematically reviews existing literature on PMDD using Robins and Guze’s criteria for the validity of a psychiatric diagnosis (clinical description, laboratory study, exclusion of other disorders, follow-up study, and family study). Despite the early recognition of premenstrual syndrome (PMS) in the 1950s, the research has suffered due to two groups of proponents viewing it with psychologizing bias and medicalizing bias. PMDD is currently understood as the severest form of PMS having psychological features. Recent evidence suggests that PMDD perhaps has neurodevelopmental underpinnings (Attention deficit hyperactive disorder, Adverse childhood experiences) affecting the fronto-limbic circuit that regulates the emotions and the individuals additionally have increased sensitivity to gonadal-hormonal fluctuations as noticed during premenstrual, pregnancy and peri-menopausal phases of life. The prevalence is comparable between high-income and low-and-middle-income countries (LAMIC), refuting the notion that it is an illness of modern women; rather greater prevalence is observed in LAMIC. Despite awareness among educated women, poor help-seeking is prominent as they perceive it as an isolating experience due to profound internalized stigma and discrimination in the workplace. Future studies must aim to develop culturally validated assessment tools and more research to understand the life course of the illness, besides systematically examining for more biological validators (animal models, genetics, imaging, neurotransmitters).